2015
DOI: 10.1116/1.4919410
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene as a model system to probe the impact of ambient gas chemistry on polymer surface modifications using remote atmospheric pressure plasma under well-controlled conditions

Abstract: An atmospheric pressure plasma jet (APPJ) was used to treat polystyrene (PS) films under remote conditions where neither the plume nor visible afterglow interacts with the film surface. Carefully controlled conditions were achieved by mounting the APPJ inside a vacuum chamber interfaced to a UHV surface analysis system. PS was chosen as a model system as it contains neither oxygen nor nitrogen, has been extensively studied, and provides insight into how the aromatic structures widespread in biological systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 73 publications
3
29
0
Order By: Relevance
“…The APPJ is similar to a previously reported design and will be overviewed here . Two electrodes (length = 2 cm) are wrapped around an alumina tube (ID = 4 mm, OD = 6.35 mm) and separated by a 1.6 cm Teflon block.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The APPJ is similar to a previously reported design and will be overviewed here . Two electrodes (length = 2 cm) are wrapped around an alumina tube (ID = 4 mm, OD = 6.35 mm) and separated by a 1.6 cm Teflon block.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, two standard liters per minute of Ar with 1% O 2 admixture is flowed through the tube into an air environment. This gas chemistry was chosen as previous work showed that O 2 admixtures to the APPJ without N 2 showed the strongest modifications and biodeactivation . The APPJ treatment was performed at 14 kV PP at 24 kHz with a gap of 9 cm among the downstream, grounded electrode, and the tube nozzle.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations